2016
DOI: 10.1111/fare.12217
|View full text |Cite
|
Sign up to set email alerts
|

Daily Poverty‐Related Stress and Coping: Associations with Child Learned Helplessness

Abstract: This study examined daily poverty‐related stress and parents' efforts to help children cope with stress in relation to learned helplessness for young children attending a Head Start preschool. A total of 750 telephone interviews were conducted with 75 parents concerning their daily stressors and strategies they used to help children cope. A behavioral protocol measured child learned helplessness. Multilevel modeling showed a positive within‐persons relationship between daily stress and coping, and a positive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Second, we supplement symptom rating scales with an overt, behavioral measure of learned helplessness, and with a composite index of chronic physiological stress (allostatic load). Few studies have examined the link between childhood disadvantage and learned helplessness (Brown, 2009; Brown et al, 2016; Evans & Cassells, 2017; Evans & English, 2002), and this is the only study to show that maturational shifts in persistence to solve challenging puzzles are compromised by childhood poverty. A critical but understudied aspect of the etiology of physical and mental well-being concomitants of childhood poverty is learned helplessness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we supplement symptom rating scales with an overt, behavioral measure of learned helplessness, and with a composite index of chronic physiological stress (allostatic load). Few studies have examined the link between childhood disadvantage and learned helplessness (Brown, 2009; Brown et al, 2016; Evans & Cassells, 2017; Evans & English, 2002), and this is the only study to show that maturational shifts in persistence to solve challenging puzzles are compromised by childhood poverty. A critical but understudied aspect of the etiology of physical and mental well-being concomitants of childhood poverty is learned helplessness.…”
Section: Discussionmentioning
confidence: 99%
“…Low-income preschool children facing a greater array of poverty-related stressors (e.g., residential mobility, unemployment) were less persistent on challenging, geometric puzzles than their peers facing fewer of these poverty-related stressors (Brown, 2009). Using a different sample of low-income children, Brown, Seyler, Knorr, Garnett, and Laurenceau (2016) found that daily fluctuations in these poverty-related stressors were tracked by task persistence at the end of each day over a 10-day period. Finally, 9-year-olds from low- versus middle-income homes were less persistent on challenging geometric puzzles (Evans & English, 2002) and this continued through age 17 (Evans & Cassells, 2017).…”
mentioning
confidence: 99%
“…Caregivers and parents of African-American young men are faced with the reality that their sons are often targeted by a biased justice system (Bobo & Thompson, 2006). Adolescents in poverty develop a sense of learned helplessness as they watch their parents struggle with the stress of making ends meet (Brown, Seyler, Knorr, Garnett & Laurenceau, 2016). For these families, having a bisexual child can bring up feelings of fear and self-blame for parents and caregivers, leading them to blame, reject and criticize their child.…”
Section: Adaptations Of Abft For Lgbq Youth Of Colormentioning
confidence: 99%
“…Indicators such as parental education, occupation, and income are only useful to the extent that they index the level of daily SES-related stress and deprivation that children face in their daily lives. Even among families below the poverty line, there is considerable heterogeneity in the level of daily poverty-related stressors that children encounter, as well as individual differences in the coping strategies employed by caregivers (Ackerman, Brown, & Izard, 2003;Brown, Seyler, Knorr, & Garnett, 2016).…”
Section: Practical and Theoretical Implicationsmentioning
confidence: 99%
“…Such an approach might be especially helpful when examining the contribution of SES to children's persistence on challenging experimental tasks such as the word learning measures in the current study. A recent study with Head Start preschoolers demonstrated that daily povertyrelated stress, but not family income-to-needs ratio, predicted children's persistence on a challenging puzzle task (Brown et al, 2016). Moreover, there is recent longitudinal evidence that persistence at least partially accounts for the relation between SES and educational outcomes (Whipple, Genero, & Evans, 2016).…”
Section: Practical and Theoretical Implicationsmentioning
confidence: 99%